Management of duct obstruction in transplanted submandibular glands. Issue 5 (May 2018) - Su, Jia-Zeng; Cai, Zhi-Gang; Liu, Xiao-Jing; Lv, Lan; Yu, Guang-Yan
Abstract: Background: Submandibular gland (SMG) transplantation is a successful treatment approach for patients with severe dry eye. However, duct obstruction can occur post-transplant. Methods: We studied nineteen patients with duct obstruction of transplanted SMGs, including five interventional modalities: stone removal; secretory stimulation (to mimic "internal irrigation" with substantial secretory flow); irrigation; surgical opening of stenosis and orifice reconstruction; cephalic vein bypass and Wharton's duct reconstruction. Results: A solitary stone was found and removed in one patient. Duct blockages like mucus plug were cleared by secretory stimulation in three patients, and by normal saline irrigation in two grafts. In the remaining 13 patients, irrigation failed and surgical opening was performed. Orifice reconstruction succeeded in six of the eight patients, whose stenosis was near the orifice. Wharton's duct reconstruction was successful in two of the five cases where stenosis was located in the middle segment of the duct. Conclusion: Transplanted SMGs obstruct for various reasons. Stone, which is easy to diagnose and treat, should be excluded first. Non-organic blockage and stenosis were semblable in clinic. Therefore, subsequent steps should be a diagnostic/therapeutic trial of secretory stimulation, followed by irrigation; failure of these interventions suggests the diagnosis of duct stenosis, necessitating surgical recanalization.